Comparison of suspension MDCK cells, adherent MDCK cells, and LLC‐MK2 cells for selective isolation of influenza viruses to be used as vaccine seeds. Issue 2 (25th October 2019) - Harada, Yuichi; Takahashi, Hitoshi; Trusheim, Heidi; Roth, Bernhard; Mizuta, Katsumi; Hirata‐Saito, Asumi; Ogane, Teruko; Odagiri, Takato; Tashiro, Masato; Yamamoto, Norio
Abstract: Background: Cell‐based influenza vaccines can solve the problem of the frequent occurrence of egg adaptation–associated antigenic changes observed in egg‐based vaccines. Seed viruses for cell‐based vaccines can be prepared from clinical specimens by cell culture; however, clinical samples risk harboring respiratory viruses other than influenza virus. Therefore, it is necessary to investigate the patterns of co‐infection in clinical samples and explore whether cell culture technology can selectively propagate influenza viruses from samples containing other respiratory viruses. Methods: A total of 341 clinical specimens were collected from patients with influenza or influenza‐like illness and analyzed by ResPlex II assay to detect 18 respiratory viruses. The patterns of co‐infection were statistically analyzed with Fisher's exact test. The samples with double or triple infections were passaged in suspension MDCK cells (MDCK‐S), adherent MDCK cells (MDCK‐A), and LLC‐MK2D cells. Cell‐passaged samples were analyzed by ResPlex II assay again to investigate whether each cell line could amplify influenza viruses and eliminate other respiratory viruses. Results: Double infections were detected in 8.5% and triple infections in 0.9% of the collected clinical specimens. We identified four pairs of viruses with significant correlation. For all samples with double and triple infection, MDCK‐S and MDCK‐A could selectively propagate influenza viruses, while eliminating all contaminating viruses. In contrast, LLC‐MK2D showed lower isolation efficiency for influenza virus and higher isolation efficiency for coxsackievirus/echovirus than MDCK‐S and MDCK‐A. Conclusions: Both MDCK‐S and MDCK‐A are considered suitable for the preparation of influenza vaccine seed viruses without adventitious agents or egg‐adaptation mutations.